EFEKTIVITAS PROGRAM MAGANG DI KANTOR AKUNTAN PUBLIK DALAM MENINGKATKAN MINAT KARIR AUDITOR MAHASISWA AKUNTANSI - Zalfa, Farah (LPPM STIE Mujahidin, 2025)
A Public Accounting Firm (KAP) is an organization that provides services, especially in the field of auditing. KAP utilizes internship programs as a way to improve operational effectiveness and office performance, as well as improve the quality of service to clients, reduce the workload of permanent staff, and optimize the use of resources by involving student interns. This community service aims to analyze the effectiveness of internship programs at Public Accounting Firms (KAP) Kumalahadi, Sugeng Pamudji & Partners in increasing the interest of accounting students to pursue a career as an auditor. The method used in this community service through this internship program collaborates with senior auditors at public accounting firms, which includes activities that can improve performance and improve audit results. The results of the community service show that the internship program provides a deeper understanding of audit practices, improves students' technical and professional skills, and strengthens their motivation to choose a career as an auditor. The main factors that influence the interest of accounting students include a professional work environment, guidance from senior auditors, and direct experience in the audit process. Thus, the internship program at KAP Kumalahadi, Sugeng Pamudji & Rekan has proven effective in shaping students' readiness and interest in pursuing a career in the audit field.